Filamentary Hierarchies and Superbubbles. I. Characterizing Filament Properties across a Simulated Spiral Galaxy - Rachel Pillsworth; Erica Roscoe; Ralph E. Pudritz; Eric W. Koch (The Astrophysical Journal)
High-resolution surveys reveal that the interstellar medium in the Milky Way and nearby galaxies consists of interlinked hierarchies of filamentary structure and superbubbles extending from galactic to subparsec scales. The characterization of filament properties across this hierarchy is of fundamental importance for the origin of giant molecular clouds and their star clusters. In this paper, we characterize the properties of filaments greater than 25 pc in length that are produced in the multiscale galactic MHD simulations of B. Zhao et al. By adapting the FilFinder algorithm of E. W. Koch & E. W. Rosolowsky, we extract over 500 filaments ranging up to 10 kpc in scale, to derive the probability distribution functions for filament masses and lengths, magnetic field orientations, and the gravitational stability and fragmentation patterns of filaments. We find power-law distributions for filament masses and lengths. The former has a power-law index α _m  = 1.85 that is nearly identical to that of observed giant molecular cloud (GMC) mass functions in extragalactic and Galactic surveys, suggesting that GMC properties are inherited from their host filaments. The fragmentation of magnetized filaments on 200 pc scales or less occurs when they exceed an average critical line mass, as predicted by theory. On larger scales, however, kiloparsec filaments form out of the cold neutral medium, and fragmentation follows local variations in the critical line mass along spiral arms or at the boundaries of superbubbles.